The essential iron-sulfur protein Rli1 is an important target accounting for inhibition of cell growth by reactive oxygen species - Alhebshi, Alawiah; Sideri, Theodora C.; Holland, Sara L.; Avery, Simon V. (American Society for Cell Biology, 2012)
Oxidative stress mediated by reactive oxygen species (ROS) is linked to degenerative conditions in humans and damage to an array of cellular components. However, it is unclear which molecular target(s) may be the primary “Achilles’ heel” of organisms, accounting for the inhibitory action of ROS. Rli1p (ABCE1) is an essential and highly conserved protein of eukaryotes and archaea that requires notoriously ROS-labile cofactors (Fe-S clusters) for its functions in protein synthesis. In this study, we tested the hypothesis that ROS toxicity is caused by Rli1p dysfunction. In addition to being essential, Rli1p activity (in nuclear ribosomal-subunit export) was shown to be impaired by mild oxidative stress in yeast. Furthermore, prooxidant resistance was decreased by RLI1 repression and increased by RLI1 overexpression. This Rlip1 dependency was abolished during anaerobicity and accentuated in cells expressing a FeS cluster–defective Rli1p construct. The protein’s FeS clusters appeared ROS labile during in vitro incubations, but less so in vivo. Instead, it was primarily 55FeS-cluster supply to Rli1p that was defective in prooxidant-exposed cells. The data indicate that, owing to its essential nature but dependency on ROS-labile FeS clusters, Rli1p function is a primary target of ROS action. Such insight could help inform new approaches for combating oxidative stress–related disease.